Chapter Lavoro e ozio in Richard Baxter - De Marco, Pietro (Firenze University Press, 2025)
In the author's opinion, Baxterian vision of work is not a modern one (if by modern we mean secularized or even just secularizing vision), what its 'history of effects' may have been. On the one hand, given the Calvinian liquidation of sacramental ontology (the Entzauberung hypothesized by Max Weber is above all a theological act), a true personal relationship to Christ is thematized in the Reformed faithful. For decades, specialist literature has been reminding us that the 'puritan' subject is not only in the cosmos. On the other hand, a peculiar extension of the evangelical command is defined, for which the service of God extends beyond "preaching, hearing, reading, praying" to the daily reality of the godly man, essentially a man at work. Avoiding idleness is a practical guarantee of Christian life.